Optimisation of yield and molecular weight of β-glucan from barley flour using response surface methodology. (March 2015) - Gangopadhyay, Nirupama; Hossain, Mohammad B.; Rai, Dilip K.; Brunton, Nigel P.
Abstract: The optimum conditions to maximize yield and molecular weight of β-glucan from Irish grown barley were determined using response surface methodology. The independent variables investigated were temperature, pH and their interaction on the extraction of β-glucan. Preliminary experiments indicated the best solid to liquid ratio and extraction time to be 1:5 and 4 h respectively. The model predicted that a temperature of 55.7 °C and pH 6.6 were optimal for maximising the yield and molecular weight of β-glucan. The reliability of the method was confirmed by performing experiments under optimal conditions and the experimental values were found to be in close agreement with the values predicted from the developed quadratic polynomial equation (average mean deviation (E) of 1.8% for extraction yield and 1.59% for molecular weight). Highlights: High yield and high molecular weight β glucan extracts from barley were achieved. RSM was useful for achieving an optimum temperature and pH for extraction. Temperature and pH had quadratic effects on yield and molecular weight of β-glucan. Solvent to flour ratio (5:1) and time (4 h) were optimised. Optimised β glucan extractions from 9 barley cultivars were presented.